THE INFLUENCE OF JOB SATISFACTION ON EMPLOYEE PERFORMANCE IN PLANNING AGENCY REGIONAL DEVELOPMENT BONE DISTRICT - Halima Thuzai; Siti Aisyah; M. Hidayat (International Journal of Economic Research and Financial Accounting, 2024)
This study aims to determine the effect of job satisfaction on employee performance at the Regional Development Planning Agency in Bone Regency. The type of research used in this research is descriptive quantitative. The data processed are the results of distributing questionnaires to employees at the Regional Development Planning Agency Office in Bone Regency with a sample used of 32 respondents. The data analysis techniques used in this study are validity and reliability tests, coefficient analysis and simple linear regression. The results showed that the job satisfaction variable had a positive and significant effect on employee performance at the regional development agency of Bone Regency with a Significant value of 0.000 <0.05 and the coefficient of determination test with an R Square value or coefficient of determination of 0.072, and an Adjusted R Square value of 0.830 or with an influence level of 83% and 17% influenced by the limitations of this research model. Based on the results of this study, there is an Influence of job satisfaction on employee performance at the Regional Development Planning Agency of Bone District.